Developing a mobile application for arabic grammar learning / Siti Nurizzaty Aimi Mohd Salleh - Mohd Salleh, Siti Nurizzaty Aimi (2020)
Arabic grammar is one of the important knowledge in learning Arabic language. It can help Muslims to understand the content of Al-Quran. Some people found that Arabic grammar is difficult and confusing in order to get a grasp of the knowledge. On the other hand, leaners faced difficulties in learning Arabic grammar due to limited hours of learning in the class and the less attractive of teaching materials. Thus, this study is aimed to design and develop a mobile application for Arabic grammar learning. Then, the usability of the mobile application is evaluated using usability test. The ADDIE Model has been used as the methodology where this model consists of five phases which are analyze, design, development, implementation, and evaluation. In each phase, the activities, techniques or software used, and the deliverables will be determined by the researcher in order to design and develop a good mobile application. This study also shows that the adaptation of multimedia elements in the mobile application can make the mobile application become more attractive and interactive for learners. The researcher has decided to use Adobe Animate for developing the mobile application. The findings from the usability testing shows that the application has the potential to be used as an Arabic grammar learning tool.